Teachers' evaluation of formative assessment on summative assessment in undergraduate medical education (Bangladesh Journal of Medical Education, 2014)
Background: Assessment is important in all forms of learning. Formative assessments have evolved as a means to adapt to student needs. Summative assessment designed to make judgments about students' performance and produce grades Formative assessment is the assessment that takes place during a course or programming of study whereas summative assessment is normally carried out at or towards the end of a course. Objective: To determine the teachers' view about the influence of formative assessment on the result of summative assessment in undergraduate medical course. Method: This cross sectional descriptive study was carried out from July 2009 to June 2010 over 106 teachers of selected two government and two private medical colleges. A structured and pretested questionnaire included different opinion about the influence of formative assessment on summative assessment was distributed among respondents and data were collected for analysis. Results: This study revealed that majority of the teachers (77%) considered feedback from formative assessment to students is important to close up the learning gap. Eighty two percent teachers were in agreement that through formative assessment teachers identified students' weak point and 69% supported that formative assessment motivates the students for deep learning and regular study. However, frequent formative assessment hampers students' independent learning which produces negative effects in summative exam. Conclusion: Formative assessment has got significant effect on summative assessment in various aspects. DOI: http://dx.doi.org/10.3329/bjme.v3i1.18591 Bangladesh Journal of Medical Education Vol.3(1) 2012: 18-21